FEM analysis of the effects of cooling techniques on the microstructure of aluminum 7075 friction stir welded joints - Ammouri, A.H. (2012)
Friction stir welding (FSW) is a proven solid-state technique for joining metal alloys. Given the low melting temperatures of light alloys, excessive heat build-up in such joints may have undesirable consequences such as melting and/or undesired grain growth. It is widely recognized that the resulting mechanical properties of a welded joint depends to a great extent on microstructure development. The aim of this paper is to improve the microstructure of friction stir welded aluminum alloy joints by utilizing two different cooling techniques. To this end, a 3D FEM model is developed to simulate the friction stir welding plunging and advancing phases. The parameters used in the FEM model were optimized for minimum simulation time and resulting in accurate simulations as compared with experimental results previously published by other workers. The work material was modeled as a visco-plastic material and dynamic recrystallization was implemented and added to the material model. Two main cooling techniques were compared: temperature controlled backing plate and another via cryogenic CO2 direct nozzle. The monitored output parameters were: temperature, stress, strain, and strain rate. Consequently, values of the Zener-Hollomon parameter, Z, were calculated and the resulting grain size distribution in the joint was found. Due to dynamic recrystallization, nano-sized grains were predicted to be generated in the cryogenically cooled weld line when compared to non-cooled one.